2015
DOI: 10.1681/asn.2014070724
|View full text |Cite
|
Sign up to set email alerts
|

Classifying AKI by Urine Output versus Serum Creatinine Level

Abstract: Severity of AKI is determined by the magnitude of increase in serum creatinine level or decrease in urine output. However, patients manifesting both oliguria and azotemia and those in which these impairments are persistent are more likely to have worse disease. Thus, we investigated the relationship of AKI severity and duration across creatinine and urine output domains with the risk for RRT and likelihood of renal recovery and survival using a large, academic medical center database of critically ill patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
355
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 435 publications
(390 citation statements)
references
References 19 publications
24
355
2
9
Order By: Relevance
“…Serial daily weights would have been more useful, but unfortunately these data are not available. Similar to data [9,10] reported in adults, oliguria at both the start and at the end of CRRT was a poor prognostic factor and was associated with mortality.…”
supporting
confidence: 84%
“…Serial daily weights would have been more useful, but unfortunately these data are not available. Similar to data [9,10] reported in adults, oliguria at both the start and at the end of CRRT was a poor prognostic factor and was associated with mortality.…”
supporting
confidence: 84%
“…Regardless of disease severity, these studies demonstrate that complete and sustained reversal of an AKI episode within 48-72 h of its onset is associated with better outcomes than longer durations of AKI [10][11][12][13][14][15] . Based on the available data and expert opinion, the workgroup proposes using 48 h to define rapid reversal of AKI…”
Section: Persistent Aki Transient Versus Persistent Akimentioning
confidence: 77%
“…Although previous studies have relied primarily on serum creatinine to identify AKI, the workgroup recommends also using urine output criteria as recommended by KDIGO 5 . The importance of urine output criteria in defining persistent AKI was confirmed in a 2015 study of 32,045 critically ill patients, which demonstrated that short-term and long-term risk of death or RRT is greatest for patients who meet both the serum creatinine and urine output criteria for AKI and experience these abnormalities for longer than 3 days 12 .…”
Section: Persistent Aki Transient Versus Persistent Akimentioning
confidence: 98%
“…In current clinical practice, the diagnosis and classification of AKI stages relies on serum creatinine, glomerular filtration rate (GFR), and urine output 1.…”
Section: The Necessity Of Early Biomarkers In Acute Kidney Injury Andmentioning
confidence: 99%